Perspectives of parents, learners and educators from Vanderbijlpark secondary schools on obligatory prescribed school uniforms - Wilken, Ilani (My University, 2010)
INTRODUCTION: Supporters of school uniforms argue that uniforms serve as a social and economic equaliser, reducing competition regarding clothing and reducing demands on parents to buy expensive, trendy clothes. Other benefits mentioned are functionality, time saving, appearance, safety, and improved academic standards and behaviour. Opponents of school uniforms differ maintaining that compulsory uniform infringes on learners’ constitutional rights to self-expression. The problem statement encompasses the desirability and viability of obligatory school uniforms in South Africa. AIM: The broad aim of this study is to determine the perspectives of parents, learners and educators at public schools in Vanderbijpark on obligatory school uniforms. METHODOLOGY: A structured questionnaire was used to gather data. Section 1 comprised general information, section 2 dealt with the advantages and disadvantages of obligatory school uniforms and section 3 contained options for more trendy school uniforms. A random stratified sample of learners in two grade 10 classes and their parents and educators was chosen from four selected schools. RESULTS: Most of the parents were between 41 and 45 years of age, by far the majorities was white, nearly a quarter had a diploma/certificate and another quarter a degree, nearly three-quarters were married or traditionally married, and nearly a third spent R901-R1200 per year on school uniforms. Most parents and educators and nearly two-thirds of the learners were highly in favour of school uniforms. Regarding the advantages and disadvantages of eight factors with reference to obligatory school uniforms as perceived by parents, learners and educators, the educators rated seven of the eight factors higher than parents and learners did, while parents rated the same factors higher than learners did, implying that learners were the least positive. The order in which they ranked the advantages was often the same or similar. They all ranked the competition aspect first, the academic aspect seventh and the economic aspect eighth, while functionality was ranked either third or fourth. Regarding preferences for more trendy uniforms, three-quarter pants and sandals were rated very low in popularity. All the stakeholders were in favour of the more traditional pants, shirt and proper shoes for both boys and girls, with a slightly more informal jacket instead of the traditional blazer.
Thesis (M. Tech. (Fashion, Dept. of Visual Arts and Design)) -- Vaal University of Technology.
Keywords: School uniforms; Compulsory school uniforms; Public schools - Uniforms